DES as a green solvent to prepare 1, 2-bis-organylseleno alkenes. Scope and limitations. Issue 49 (9th December 2015) - Lopes, Eric F.; Gonçalves, Lóren C.; Vinueza, Julio C.G.; Jacob, Raquel G.; Perin, Gelson; Santi, Claudio; Lenardão, Eder J.
Graphical abstract: Abstract: We describe here our results on the use of choline chloride/urea 1:2 as a deep eutectic solvent (DES) in the synthesis of vinyl selenides. A good selectivity for the ( E )-1, 2-bis-organylseleno alkenes was observed starting from terminal alkynes and diaryl or dibutyl diselenides in the presence of NaBH4 . The reaction of 1, 3-butadiynes with diphenyl diselenide afforded exclusively the respective mono-selenylated ( Z )-alkenynes. Diphenyl ditelluride reacted with phenylacetylene and 1, 4-diphenyl-but-1-en-3-yne affording ( Z )-phenyltelluro alkenes in good yields.